Encruzilhadas de gênero e raça: sub-representação de mulheres negras nos partidos políticos brasileiros - Oliveira, Fernanda Cordeiro de (Universidade Federal de São Carlos, 2025)
When investigating the participation of black women in Brazilian politics, even after the creation of the Quota Law, n. 9.504/97, it appears that they are still underrepresented, which presents itself as a problem. Several elements seem to contribute to this situation. However, the form of organization of political parties, with an oligarchic and bureaucratized structure, is directly connected to this underrepresentation, since party associations are the main routes of access to the legislative and the executive branches of the Brazilian government. Thus, it is a challenge to modify this scenario in intra-party politics, which justifies the research developed. In this context, the main objective of the investigation is to ascertain how political parties in Brazil have promoted or constrained the access of black women to institutional politics. This is a qualitative and quantitative research, which analyzes data on the presence of black women in senior management positions of Brazilian political parties in 2016, 2020 and 2024, with data from the STI/TSE. Through documentary research, the statutes of the twenty-nine political parties registered with the Superior Electoral Court in 2024 are also examined, plus two more incorporated parties, between August and November of that year, as well as their internal regulations and websites, to ascertain the existence of sectors and secretariats that deal with gender and ethnic-racial issues in these parties. This is relevant to understand the level of commitment of political parties on promoting the inclusion of black women. The bibliographic research was based on references that discuss the presence of black women in politics, political parties, structural racism, intersectionality and political violence of gender and race. Through this analysis, a situational diagnosis was made, resulting in the confirmation of the hypothesis that the oligarchic character of political parties contributes to gender and race inequality within party associations and is reflected in politics. In view of this context and the insufficiency of quotas to account for the increase in political participation of black women, we propose that, within the political parties, the intersectional analytical tool is used to elaborate public policies that seek to mitigate the problem of this underrepresentation.
Crossroads of gender and race: underrepresentation of black women in Brazilian political parties
Keywords: Mulheres negras; Sub-representação; Partidos políticos; Interseccionalidade; Black woman; Underrepresentation; Political parties; Intersectionality; CIENCIAS HUMANAS::CIENCIA POLITICA